479 Chronic Subdural Hematomas Treated With Surgical Evacuation Versus Standalone Middle Meningeal Artery Embolization: Volumetric Resolution in Immediate, Early and Late Follow-Up in a Propensity Matched Cohort. (April 2023) - Housley, Steven B.; Monteiro, Andre; Khawar, Wasiq; Donnelly, Brianna; Lian, Ming; Fritz, Alexander; Baig, Ammad; Waqas, Muhammad; Cappuzzo, Justin Mark; Snyder, Kenneth Vincent; Siddiqui, Adnan Hussain; Levy, Elad I.; et al.
Abstract : INTRODUCTION: Literature comparing surgery and middle meningeal artery embolization (MMAE) for chronic subdural hematomas (cSDH) is limited by patient selection bias. Furthermore, most studies do not perform volumetric measurements over time when comparing these two modalities. METHODS: Retrospective search of our database to include cSDH patients managed with either SEA or standalone MMAE. Propensity-score-matching was performed for axial and coronal lengths, maximum diameter and midline shift. Volumes of cSDH were measured at 24 h post-procedure, 3-12-weeks, 12-24-weeks, 24-36-weeks, 36-48-weeks and 48-60-weeks. RESULTS: Forty-eight matched hematoma pairs were obtained. The groups were also similar in demographics, comorbidities, medications and symptoms. Median volume was significantly lower at 24 h in the SEA group (SEA, 12.6 mL vs MMAE, 52.7 mL, P < 0.001). Median volume reduction was significantly greater in the SEA group at 24 h (SEA, 39.1 mL vs MMAE, 8.8 mL, P < 0.001) and in the 3-12 weeks interval (SEA, 50.8 mL vs MMAE, 23.7 mL, P < 0.001). The SEA group had significantly greater median resolution rate at 24 h (39.1 mL/day vs 8.8 mL/day, P < 0.001) and in the 3 to 12 weeks interval (1 mL/day vs 0.4 mL/day, P < 0.001) but not in remaining intervals. Near complete resolution at the 3 to 12 interval (SEA, 26.1% vs MMAE, 28%, P = 1) and 12 to 60 weeks interval (SEA, 78.3% vs MMAE, 80%, P = 1) was not significantly different between the groups. Overall, the recurrence was significantly higher in the SEA group than in the MMAE group (22.9% vs 4.2%, P = 0.01). CONCLUSIONS: In comparable cSDH patients, surgical evacuation resulted in better volumetric outcomes in the immediate and early follow-up periods but in extended follow-up intervals. Furthermore, surgical patients experienced a significantly higher rate of recurrence.